MARKETING RESEARCH INTRODUCING NEW GOODS TO THE AGRICULTURAL PRODUCT MARKET - Войтенко, Олександра А.; Жигалкевич, Жанна М. (Journal of Strategic Economic Research, 2024)
The article explains the concept of "new product". The most used classifications of the new product and their advantages were studied in detail. An in-depth study of the scientific approaches to bringing a new product to the market helped to understand the essence of the "removal" process. The work is entirely devoted to the marketing research of the introduction of organic sunflower oil to the market of organic sunflower oil, in particular for a domestic enterprise. Search questions related to the analysis of the organic sunflower oil market in Ukraine, the analysis of the main competitors and the analysis of consumer behavior were formed. An in-depth analysis of the state of the agricultural products market made it possible to identify the main problems and trends. A careful study of the market of organic agricultural products showed that Ukraine is one of the leading exporters in this market in the world. The main principles of organic farming have been revealed. The supply and demand for organic agricultural products is comprehensively considered. A detailed analysis of the impact of legislative actions by the state outlined the barriers to entering the market, namely: the creation of a register of organic producers with the necessary certification and the opening of the land market. The increase in prices for logistics, dependence on yield, subsidies from the state, dependence on the location of industrial enterprises, etc. and their impact on the activities of organic operators are also reviewed. In order to solve the marketing management problem of introducing a new product to the market, a marketing study was conducted. The market of organic oil was carried out, the main competitors in the market were determined and consumer behavior was studied. The obtained results of the cabinet study showed that Ukraine is the leader in the export of traditional sunflower oil in the world. Three main competitors were identified and information on their activities was provided. Consumer behavior was comprehensively investigated by the method of in-depth interviews. Insiders were obtained, a list of factors by which consumers choose a supplier was formed, and the process of making a decision to buy organic sunflower oil was described.